The Acute Physiological and Perceptual Responses Between Bodyweight and Treadmill Running High-Intensity Interval Exercises - Bellissimo, Gabriella F.; Ducharme, Jeremy; Mang, Zachary; Millender, Desmond; Smith, Jessica; Stork, Matthew J.; Little, Johnathan P.; Deyhle, Michael R.; Gibson, Ann L.; de Castro Magalhaes, Flavio; Amorim, Fabiano (Frontiers in Physiology, 2022)
Objective: The purpose of this study was to compare the acute physiological, perceptual, and enjoyment responses between bodyweight high-intensity interval exercise (BW-HIIE) and treadmill running high-intensity interval exercise HIIE (RUN-HIIE). Methods: Twelve adults [age: 29.5 ± 5.3 years; weight: 70.9 ± 15.0 kg; height: 167.9 ± 8.9 cm; peak oxygen consumption (VO2 peak): 48.7 ± 6.5 mL· min-¹·kg-¹)] performed both RUN-HIIE and BW-HIIE. RUN-HIIE consisted of 2 sets of 5, 60-second (s) run intervals at 100% of the speed achieved during VO2 peak testing followed by 60s of walking at 4.02 kilometers per hour (km/h). BW-HIIE consisted of 2 sets of 5, 60s ‘all-out’ effort calisthenic exercises followed by 60s of marching in place at 100 steps per minute. Oxygen consumption (VO2), blood lactate (Blac), heart rate (HR), and rating of perceived exertion (RPE) were measured during exercise. Physical activity enjoyment (PACES) was assessed post exercise. Creatine Kinase (CK) was measured before exercise and 48-hours post-exercise. Muscle soreness was assessed before exercise, post exercise, and 48-hrs post-exercise. Results: Oxygen consumption relative to VO2 peak was higher (P < 0.001) during RUN-HIIE (88 ± 3%) compared to BW-HIIE (77 ± 4%). HR relative to HRpeak was higher (P = 0.002) for RUN-HIIE (93 ± 1%) compared to BW-HIIE (88 ± 2 %). Blac was higher (P < 0.001) after BW-HIIE (11.2 ± 3.2 mmol/L) compared to RUN-HIIE (6.9 ± 2.0 mmol/L). Average RPE achieved was higher (P = 0.003) during BW-HIIE (16 ± 2) than RUN-HIIE (14 ± 2). PACES was similar for RUN-HIIE and BW-HIIE (P > 0.05). No differences (P > 0.05) in CK were observed between RUN-HIIE or BW-HIIE. Conclusion: Our results indicate ‘all-out’ calisthenic exercise can elicit vigorous cardiorespiratory, Blac, and RPE responses. Implementing this style of exercise into training requires minimal space, no equipment, and may elicit cardiometabolic adaptations seen with traditional forms of high-intensity exercise.